High Mass Resolution fs-LIMS Imaging and Manifold Learning Reveal Insight Into Chemical Diversity of the 1.88 Ga Gunflint Chert - Lukmanov, Rustam A.; de Koning, Coenraad; Schmidt, Peter Keresztes; Wacey, David; Ligterink, Niels F. W.; Gruchola, Salome; Grimaudo, Valentine; Neubeck, Anna; Riedo, Andreas; Tulej, Marek; Wurz, Peter (Frontiers in Space Technologies, 2022)
Extraction of useful information from unstructured, large, and complex mass spectrometric signals is a challenge in many application fields of mass spectrometry. Therefore, new data analysis approaches are required to help to uncover complexity of such signals. In this contribution, we examined the chemical composition of the 1.88 Ga Gunflint chert using the newly developed high mass resolution laser ionization mass spectrometer (fs-LIMS-GT). We report results on: 1) Mass-spectrometric multi-element imaging of the Gunflint chert sample; 2) Identification of multiple chemical entities from spatial mass spectrometric data utilizing non-linear dimensionality reduction and spectral similarity networks. The analysis of 40’000 mass spectra reveals the presence of chemical heterogeneity (7 minor compounds) and two large clusters of spectra registered from the organic material and inorganic host mineral. Our results show the utility of fs-LIMS imaging in combination with manifold learning methods in studying chemically diverse samples.